Nomenclatural Changes in Australian Tettigoniidae - Rentz, D. C. F. (Zootaxa, 2009)
During the course of preparing a Guidebook to Australian Tettigoniidae, a number of name changes became necessary as follows. The combinations and the type relevant specimens can be viewed soon on the Orthoptera Species File, Eades & Otte (2009).